Herbicidal tolerance of Trichoderma spp a potential biocontrol agent of soil borne plant pathogenas - KWALKO, SURAJIT; SUBHALAKSMI, THANGJAM; JASH, SUBHENDU; BOSE, SHAONLI; PAN, SITANSU (The Indian Journal of Agricultural Sciences, 2011)
Use of biocontroi agents, Trichoderim and Gliocluditum spp is thc eco-friendly approach for protection of many crop plants against a wide range of soil borne plant pathogens causing seed rot, damping off. root rot and wilt (Pan and Jash 2004, Jash 2006).